1995
DOI: 10.1136/thx.50.2.165
|View full text |Cite
|
Sign up to set email alerts
|

Chest physiotherapy in cystic fibrosis: a comparative study of autogenic drainage and the active cycle of breathing techniques with postural drainage.

Abstract: Background -Autogenic drainage has been suggested as an alternative method of chest physiotherapy in patients with cystic fibrosis. In this study autogenic drainage was compared with the active cycle of breathing techniques (ACBT) together with postural drainage. Methods -Eighteen patients with cystic fibrosis took part in a randomised two-day crossover trial. There were two sessions of one method of physiotherapy on each day, either autogenic drainage or ACBT. The study days were one week apart. On each day t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
38
2
8

Year Published

1998
1998
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 86 publications
(48 citation statements)
references
References 15 publications
0
38
2
8
Order By: Relevance
“…Also, there was no significant deterioration in PEFR during and immediately after each intervention period. This contradicts Miller et al 31) , who reported in 1995 that pulmonary function was decreased after inhalation of aerosol, presumably due to bronchoconstriction. In our study, all subjects seemed to be in stable conditions throughout the study period of three study days and d i d n o t h a v e a n y a d v e r s e e f f e c t d u e t o bronchoconstriction.…”
Section: Discussioncontrasting
confidence: 53%
“…Also, there was no significant deterioration in PEFR during and immediately after each intervention period. This contradicts Miller et al 31) , who reported in 1995 that pulmonary function was decreased after inhalation of aerosol, presumably due to bronchoconstriction. In our study, all subjects seemed to be in stable conditions throughout the study period of three study days and d i d n o t h a v e a n y a d v e r s e e f f e c t d u e t o bronchoconstriction.…”
Section: Discussioncontrasting
confidence: 53%
“…Desaturation has been described during CPT. 5,29 It has been suggested that desaturation can be prevented by allowing sufficiently long periods of quiet breathing between the FET maneuvers. 7 In our study, desaturation occurred immediately after the FET maneuvers during the control session, consistent with a role of bronchial collapse and prolonged expiration.…”
Section: Spomentioning
confidence: 99%
“…One group has compared AD and the ACBT [64] and concluded that AD increased the rate of clearance of mucus, although there was no overall difference in the weight of sputum expectorated. There is debate, however, as to whether it was the ACBT which was used in the study in practice [65,66].…”
Section: Autogenic Drainagementioning
confidence: 99%